THE EFFECT OF INCOME, SOCIALIZATION, TAXPAYER AWARENESS, AND TAX SANCTION ON THE COMPLIANCE OF LAND AND BUILDING TAX PAYMENT AT DUKUH PENGKOL - Oceania Andika Putri; Ismunawan Ismunawan (Universitas Airlangga, 2021)
This study aims to analyze the factors that influence compliance with land and building tax payments. The independent variables used are income, socialization, taxpayer awareness, and tax sanctions. This research was conducted on land and building taxpayers who are in Dukuh Pengkol. The method used in the collection of samples is purposive sampling with a sample size of 91 taxpayers. In collecting data using a questionnaire that is distributed using google form. The analytical tool used in this study is multiple linear regression and processed using SPPS Ver. 22.0. The results of this study indicate that, taxpayer income, taxpayer awareness, and tax sanctions have a significant and significant effect on compliance with land and building tax payments in DukuhPengkol. Meanwhile, tax socialization had no effect on compliance with land and building tax payments at Dukuh Pengkol.